Triorchidism with vascular anomalies in a child: A surgical case report - Driss Tahiri; Najoua Aballa; Mohamed Oulad Saiad (Urology Case Reports, 2025)
Triorchidism, the most frequent form of polyorchidism, is a rare congenital anomaly with three testes. We report a case of an 18-month-old boy with right cryptorchidism. Surgery revealed two ipsilateral testes: one well developed, and the other hypoplastic, classified as Leung type IV with shared vascular connections. The hypoplastic testis was excised while orchiopexy preserved the dominant one. Histopathology confirmed atrophy without malignancy. At 12-month follow-up, the preserved testis showed vascularization and growth. This case highlights the surgical challenges of triorchidism with cryptorchidism and atypical vascular anatomy, requiring a balance between oncologic risk and functional preservation.